Developing English Speaking Skills of 4th Year Students by Using the Cooperative Learning Strategy on Team-Pair-Solo Technique A Case Study of Faculty of Education, Souphanouvong University: https://doi.org/10.69692/SUJMRD0802127 - KEOPHASITH, Vatsana; PANFONGPHET, Sipaseuth; XUAMOLEE, Thongsy; PHUANGSAVTH , Vatthana; PHOMMANITH , Khamsone (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purposes of this study were to (1) study the effectiveness of using the cooperative learning strategy on team-pair-solo technique to enhance the students’ English speaking skills, and (2) to investigate the students’ satisfaction with the use of its teaching technique. The target groups consisted of 19 students from the fourth-year majoring in mathematics in the first semester, academic year 2020-2021 at Department of Mathematics, Faculty of Education. The instruments used in this research consisted of 4 five-hour lesson plans, one students’ English speaking skills assessment form, one English speaking skills test, one observation check list, and one questionnaire about students’ satisfaction. The obtained data were analyzed to calculate means, standard deviation and t-test (dependent samples) by SPSS program, version 21.0. The findings were as follows: Overall, the students’ English speaking ability was significantly higher after learning with the use of cooperative learning strategy on team-pair-solo technique, at the 0.05 level, indicating that the teaching strategy was effective in enhancing students’ English-speaking skills, and generally, the students’ were satisfied with their improvement in English speaking through the use of cooperative learning strategy on team-pair-solo technique, which is viewed at a high level.